Qualche riflessione su istituzione e tutela dei diritti (Società e diritti, 2023)
AbstractMy paper is devoted to the philosophical-legal premises of the institution of rights. In the first part, I will deal with the institution of law as Kulturarbeit, while in the second part I will thematize the transition from law to rights and the necessary (and increasingly problematic) protection of the latter.